Thunderstorm phobia in dogs - Wallentine, Kari D. (Kansas State University, 2011)
Canine thunderstorm phobia is a common, frustrating, and complex problem that, due to the often severe nature of the clinical signs, can lead to canine relinquishment to shelters. Although a potentially treatable disorder, existing treatment options have several limitations and variable success rates. Three survey-based studies were conducted to increase the knowledge base for canine thunderstorm phobia. The first study distributed 1445 surveys through 16 Kansas veterinary clinics to determine the prevalence and characteristics of thunderstorm phobic dogs and assess differences between affected and non-affected dogs. Of 463 dogs surveyed, 240 were thunderstorm phobic as assessed by their owners. Severe weather warning systems may play a role in thunderstorm phobia. Thunderstorm phobic dogs were more fearful when exposed to tornado sirens, both during actual storms and siren testing, indicating a possible effect of classical conditioning. No differences were noted regarding sex, breed, pedigree, or neuter status. Most affected dogs preferred to be indoors remaining near their owners. The second study distributed 1600 surveys through eight Kansas animal shelters to determine the prevalence of relinquished dogs with thunderstorm phobia. Other reasons for relinquishment were also assessed. A fear of thunder was among the least common behavioral problems leading to relinquishment in dogs. Only a quarter of owners had visited a veterinarian for assistance with behavioral problems. The third study involved the administration of dog appeasing pheromone (DAP) in a double-blind, placebo-controlled, randomized clinical trial to assess its efficacy as a sole treatment for thunderstorm phobia. Data was collected from 60 dog owners using behavioral assessment questionnaires. In dogs given the placebo, six behaviors significantly improved, with another eleven showing a numerical trend toward improvement. However, in dogs given DAP, significant improvement was seen in three of these same behaviors. Consequently, these results do not indicate the potential use of DAP for reducing fearful behaviors associated with thunderstorm phobia when compared to negative controls. Information gained from these studies allows veterinarians and behavioral researchers to better understand the extent of this behavioral disorder and hopefully stimulates future research to find new and more effective ways to treat it.
Keywords: Dog; Thunderstorm; Relinquishment; Fear; Behavior; Pheromones; Animal Sciences (0475)